1992
DOI: 10.3181/00379727-199-43363
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cortical Intermediary Metabolism in the Recovery Phase of Postischemic Acute Renal Failure in the Dog

Abstract: Renal metabolism has been studied in eight dogs before and 48 hr after a 60-min period of renal ischemia induced by clamping the left renal artery with the simultaneous removal of the right kidney, and in 12 sham-operated animals. The study involved the measurement of renal uptake and production of lactate, glutamine, glutamate, alanine, ammonium, and oxygen, and the measurement of the tissue concentrations of ATP, glutamine, lactate, alpha-ketoglutarate, aspartate, and alanine in the renal cortex. Two days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Specifically, ACC in canines in the presence of inhibition of vasodilating prostaglandins induced reductions in GFR in association with renal vasoconstriction with tubular vacuolization and marked increase in apoptotic cell death. Though the duration of the study was short and physiological parameters were only collected 2 hour post-ischemia, we observed moderate loss of GFR, which is in line with published studies in AKI long-term studies such as post-ischemia for 48 hours 32,33 . We believe the promising results obtained from this short-term study will guide us in the design of more long-term studies, such as 2 or 7 days post-ischemia AKI, to evaluate CRRL269's therapeutic potential more extensively.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, ACC in canines in the presence of inhibition of vasodilating prostaglandins induced reductions in GFR in association with renal vasoconstriction with tubular vacuolization and marked increase in apoptotic cell death. Though the duration of the study was short and physiological parameters were only collected 2 hour post-ischemia, we observed moderate loss of GFR, which is in line with published studies in AKI long-term studies such as post-ischemia for 48 hours 32,33 . We believe the promising results obtained from this short-term study will guide us in the design of more long-term studies, such as 2 or 7 days post-ischemia AKI, to evaluate CRRL269's therapeutic potential more extensively.…”
Section: Discussionsupporting
confidence: 89%
“…Lee and colleagues 27 demonstrated that, like humans, dogs with two kidneys subjected to 30 minutes of unilateral warm ischemia demonstrated no significant change in creatinine level or resistive index after 14 days. In 1992, Montanes and associates 28 demonstrated that 60 minutes of warm ischemia in a solitary canine kidney decreased canine The timing of drug administration was also based on previous experiments. In the seminal report on the administration of mannitol before renal ischemia, mannitol was most effective when given within 15 minutes of warm renal ischemia.…”
Section: Erythropoietin-induced Ischemic Preconditioningmentioning
confidence: 99%
“…Appropriate discrimination between IR damage and IR injury critically relies on the organ‐specific assessment of metabolic competence (i.e., prolonged normoxic glycolysis, see outline in Figure 1). Kidney‐specific metabolic profiling of the injured kidney can be achieved through renal vein–specific blood sampling using the spermatic vein as access 39,55 . Microdialysis is a potential alternative to arteriovenous sampling, but has not yet been validated for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Selective arteriovenous sampling identified normoxic glycolysis and impaired lactate handling as key characteristics of clinical renal IR injury (Table 1 ). 3 , 4 Only three experimental studies applied selective venous sampling, 3 , 34 , 39 but very limited metabolic analysis was performed.…”
Section: Discussionmentioning
confidence: 99%